SARTANS OF THE SECOND GENERATION: THERAPEUTIC POTENTIAL EXTENSION - S. V. Nedogoda (Столичная издательская компания, 2016)
Peculiarities of the treatment with angiotensin II receptor blocker telmisartan are analyzed taking into account its clinical and pharmacological characteristics. Special attention is paid to the telmisartan benefits in comparison with other sartans. Key details of telmisartan interaction with peroxisome proliferator-activated receptors (PPAR) are discussed. Mode of this interaction distinguishes pharmacodynamic effects of different medicines. On the basis of presented data author concludes that antihypertensive therapy with telmisartan provides significant benefits.